الرقابة القضائية على السلطة التقديرية للإدارة في قراراتها التأديبية - الزلافي مسعود محمد عبيد (Scientific Journal of University of Benghazi, 2021)
Granting the discplinary legislator jurisdiction in the field of ission in terms of that differ interms of the material exiistence of the fact. Where the legal conditioninfg for them becam clear to the administrative judge. Theutmost importance of the authorities that refer to the imposition of restrictions imposing restrictions imposed on imposing restrictions imposed on them. An amendment was mad to the amendment from the material existence of the legal facts. Then the scop of this judiciarys oversight was expanded to narrow the limits of the discretionary power to the maximum value of discretion.